A Methodology for Architecture Theory and Practices Research: Design Practices Evaluation Studio - Bashier, Fathi (European Journal of Sustainable Development, 2019)
This article presents the initial findings of the design research carried out during the last semester by the master of architecture students at Wollega University, Ethiopia. The research goal is the creation of new knowledge to improve the design process. The dissatisfaction with the outcomes of the conventional design approach has led to rising concern and growing awareness of the need to evaluate design outcomes and to learn from the failure. That inadequate understanding of design problems leads frequently to design failure suggests that the evaluation of design outcomes can be made by assessing the way architects develop understanding of design problems, and how they use that understanding for developing knowledge base of the design process. The assumption is that architects’ understanding of design problems can be assessed by examining the way data is used for developing the knowledge base of the design process. The students surveyed the architects’ views in order to produce knowledge, which can be used to develop methods for discovering how inadequate data contributes to miss-informed design decisions; and methods for assessing the architects’ understanding of design problems. In this article the survey findings are analyzed and documented; and, the way the insight drawn from the inquiry can be used in future research for developing design theory, is discussed. Keywords: design outcomes, failure, evaluation, questionnaire, analyze